Emerging technologies [drug eluting stents]. - Panescu, D. (IEEE Engineering in medicine and biology magazine)
Two main contributing factors to plaque formation and growth. One relates to the triggering role played by inflammatory mediators, such as cytokines. The second relates to the out-of-control growth of smooth-muscle cells. The drug selected to work with a drug-eluting stent should control one or both of these factors. Typically, the drug is entrapped in a polymer coating that slowly releases it into the arterial wall. Polymer materials include bioerodible polymers, such as poly-L lactic acid, and biostable polymers, such as polyurethane derivates and silicone-based polymers.